Document Study of UNNES Legality as Legal Entity State University - Masyhar, Ali; Maskur, Muhammad Azil; Widodo, Mulyo (JILS (Journal of Indonesian Legal Studies), 2018)
Unit of Public Service Agency (PSA Work Unit). UNNES continues to improve itself towards better community service, which is as a Legal Entity State University. Legal Entity State University will have a highly positive impact, especially the autonomy of academic and non-academic administration and management. One of the important efforts in order to achieve the status of UNNES as a Legal Entity State University, it is necessary to form a legal document that is the basis of an organization in the form of a Statute. In the preparation of the Statute, it will not be likely to obtain a suitable Statute without the study and analysis outlined in the Academic Document. Based on this background, this research was based on the formulation of the problem on what is the rationality of the Academic Document that needs to be built, in order to produce a Statute of Legal Entity State University that is suitable for UNNES? And what is the formulation/draft of the Statute of UNNES as a Legal Entity State University in order to materialize the vision of UNNES, which is the Conservation Vision-Based University and International Reputation? Based on the formulation of the problem it is intended to produce an Academic Document of the Statute of UNNES as a Legal Entity State University and the legality document of UNNES as a Legal Entity State University, especially in the form of a constitutional Draft Statute.